Studi Komparasi Kapasitas Masyarakat HKm Beringin Jaya dan HTR Hajran dalam Mengelola Sumber Daya Hutan untuk Keberlanjutan - Budi; Rina Mardiana (Jurnal Penyuluhan, 2022)
The reality of damage to forest ecosystems and poverty in people living in and around state forest areas is caused by the previous allocation policy for the use of forest resources and policies in other sectors. The combination of those policies influence the behavior / actions / attitudes of the community and forges the community to have ability or capacity to utilize and manage forest resources, inside or outside the state forest area. Previous researchs have stated that communities have the capacity to manage forest resources sustainably, but there has been no in-depth research on the components of community capacity. The research explores it by comparing the capacity of the HKm Beringin Jaya community in Tanggamus District, Lampung Province and the HTR Hajran community in Batanghari District, Jambi Province, who are managing forest resources in social forestry areas. The study used a qualitative approach supported by quantitative data. The results show that the components of community capacity in managing forest resources consist of technical, networked and cultural capacities possessed by the two communities studied with different degrees/levels. The indicators in each capacity component showed that the HKm Beringin Jaya community has a higher capacity than the HTR Hajran community. The sustainability of forest resource management in forest areas has been achieved by the Beringin Jaya HKm community.